Pemanfaatan Web Service Moodle Berbasis Rest-Json Untuk Intensitas Pengguna E-Learning - Mellan Fratama; febriyanti panjaitan (Jurnal Ilmiah Matrik, 2020)
Abstract : E-learning is one of the needs of school and university institutions. At SMK PGRI Tanjung Raja wants access to online learning (E-learning) to make it easier for teachers to distribute learning materials to students. The author will develop Moodle e-learning as a web service that can be used. To help monitor the activities carried out by the teacher, the author will use rest-json as a data collection format and will display a report format for the recapitulation of teacher activeness in online learning. The results of this study are that Moodle can be used by 3 users, namely admin as manager, teacher and students as general users, to see the results of the teacher's point report can be seen on the teacher's income menu. Keywords: : E-Learning, Moodle, Web Service, Waterfall, Rest-Json Abstrak : E-learning menjadi salah satu kebutuhan dari institusi sekolah maupun perguruan tinggi. Pada SMK PGRI Tanjung Raja menginginkan adanya akses pembelajaran online (E-learning) untuk mempermudah guru dalam membagikan materi pembelajaran kepada siswa/siswi. Penulis akan mengembangkan E-learning moodle sebagai web service yang dapat digunakan. Untuk membantu pemantauan aktivitas yang dilakukan oleh guru, penulis akan memanfaatkan rest-json sebagai format pengambilan data dan akan menampilkan format laporan rekapitulasi keaktifan guru dalam pembelajaran secara online. Hasil dari penelitian ini yaitu moodle dapat digunakan oleh 3 pengguna yaitu admin sebagai pengelola, guru dan siswa sebagai pengguna umum, untuk melihat hasil laporan poin guru dapat dilihat pada menu income guru. Kata kunci: E-Learning, Moodle, Web Service, Waterfall, Rest-Json